Medical devices biomaterials: a review - Festas, A. J. (2019)
Due to the world’s population life expectancy increase, healthcare demands in terms of quality and accessibility are higher than ever before. Concerning the manufacturing of medical devices, the development of new biomaterials, new manufacturing methods and techniques have always been on researchers focus. In the development of a medical device, the choice of the proper material to be used is of the most importance, since its ability and capacity to fulfil the expected function will determine the success of the medical device itself. This work aims to do a review of those that are the most commonly used biomaterials. After an explanation on what are biomaterials and what defines them, it is presented a more in-depth approach to each of the four major types of biomaterials: metal, polymer, ceramic and composites, where their main characteristics and preferred applications in the area of medical devices are described.